Effect of Virgin Coconut Oil Administration to Increase HDL, Decrease LDL and IL-6 in Hypercholesterol Male Wistar Rats - Meli Maulidia; Joko Wahyu Wibowo; Titiek Sumarawati (Indonesian Journal of Medicine, 2022)
Background: Hypercholesterol is a change in blood lipid profile levels, from rising cholesterol levels that can be triggered by frequent consumption of fatty foods. Hypercholesterol causes adipose tissue and macrophages to release inflammatory cytokines, then adipose cells release IL-6 and spur the formation of CRP. This study aimed to determine the effect of Virgin coconut oil (VCO) on changes in HDL, LDL, and IL-6 levels in hyper cholesterol mice.Subjects and Method: This randomized controlled trial was carried out at the PSPG UGM Nutrition Laboratory in August 2021. The total number of samples used was 20 tails and 4 spare tails, namely 24 male Wistar strain rats. Sampling using simple random sampling. The independent variables in this study were the dose of VCO 0.9 ml/200g BW/day, and 0.45 ml/200g BW/day. The dependent variables in this study were HDL, LDL, and IL-6 cholesterol levels in male Wistar rats. The data in the analysis used a normality test with the Shapiro-Wilk test and a data homogeneity test with the Levane test. HDL dan LDL levels were measured using a lysis reagent, while IL-6 was measured using the ELISA method.Results: Average LDL and HDL levels are highest in the P1 group compared to the P2, K0, and K1 groups. The One Way Anova test on HDL levels showed a significant difference between groups with p<0.001. One Way Anova test results on LDL and IL-6 levels showed significant differences between the groups (p<0.001) and (p= 0.004).Conclusion: Administering VCO at a dose of 0.9 mL/ 200 g BB/day 0.45 mL/200 g BB/day, and 86.4 mg/200 g can increase HDL and IL-6 levels in male rats Wistar strain with hyper cholesterol and lowered LDL levels by the same dose in male mice with hyper cholesterol.Keywords: hyper cholesterol, HDL, LDL, IL-6Correspondence: Meli Maulidia, Magister Ilmu Biomedik, Universitas Islam Sultan Agung Semarang. Jl. Raya Kaligawe Km.04 Semarang 50112, Central Jawa, Indonesia. Email: maulidia.dr@gmail.com. Mobile: +6285740003464.Indonesian Journal of Medicine (2022), 07(04): 471-478https://doi.org/10.26911/theijmed.2022.07.04.12